Optimization of process conditions and emulsion composition, and their effects on emulsion and encapsulation properties of spray-dried fish oil powder - Tirgar, Mina (2012)
Fish oil is the richest dietary source of long-chain polyunsaturated fatty acids (LCPUFAs), but it is prone to oxidative deterioration when exposed to oxygen. The purpose of this study was to produce microencapsulated fish oil powder using spray-drying technology. This study was performed in order to 1) screen the most suitable coating material and optimize the best emulsion formulation for the production of microencapsulated fish oil powder and 2) optimize the spray-drying parameters to produce microencapsulated fish oil powder with the best encapsulation properties. To meet the first objective, three coating materials were used: maltodextrin (15, 25% w/w), Arabic gum (2.5, 7.5% w/w), and methylcellulose (0.5, 1.5% w/w). In addition, the emulsion composition was optimized according to two factors: the fish oil content (6- 12% w/w) and the coating material (15–31% w/w) using response surface methodology (RSM). The results indicated that Arabic gum (5% w/w) had the most significant (p ˂ 0.05) effect on the surface mean diameter of the emulsion. Maltodextrin had the most significant (p ˂ 0.05) effect on the centrifugal stability of the emulsion and the amount of surface oil of the powder at 15 and 20% (w/w) respectively, whereas methylcellulose (0.5% w/w) had the most significant (p ˂ 0.05) effect on the width distribution of the droplets in the emulsion. The oil content (11% w/w) had the most significant (p < 0.05) effect on the centrifugal stability and the creaming stability of the emulsion. In addition,oil content (9% w/w) had the most significant effect on the moisture content of the powders. Whereas the interaction between the coating and the oil had the most significant (p ˂ 0.05) effects on the surface mean diameter of the powder. In the second objective, the temperature (140-200 ˚C), pressure (1-5 kgf/cm²) and feed flow rate of the emulsion (5-20 ml/min) were applied to optimize the spray-drying parameters using RSM. The results indicated that pressure had the most decreasing effect on the average particle size and the amount of surface oil at 4 and 3 kgf/cm² respectively. Moreover, pressure (4 kgf/cm²) had the most increasing effect on microencapsulation efficiency, and the interaction between this factor and the temperature revealed the most significant (p ˂ 0.05) effect on total oil extraction. The flow rate had the most significant (p ˂ 0.05) effect on the uniformity and color at 7 and 17 ml/min, respectively. No significant (p > 0.05) differences were observed between the experimental and predicted values; this verified that the used model for this study as suitable. A fish oil emulsion containing 17.30% (w/w) coating material consisting of 11.85% (w/w) maltodextrin, 4.80% (w/w) Arabic gum, and 0.65% (w/w) methylcellulose with 11.48% (w/w) oil content and 71.22% (w/w) deionized water was predicted to produce the best coating material and emulsion composition for the encapsulation of fish oil powder. An inlet temperature of 153 °C, pressure of 4 kgf/cm² and feed flow rate of emulsion of 17 ml/min were demonstrated to be the optimum conditions for producing encapsulated fish oil powder.